Fluctuating seawater pH/pCO2 regimes are more energetically expensive than static pH/pCO2 levels in the mussel Mytilus edulis. Issue 1865 (18th October 2017) - Mangan, Stephanie; Urbina, Mauricio A.; Findlay, Helen S.; Wilson, Rod W.; Lewis, Ceri
Abstract : Ocean acidification (OA) studies typically use stable open-ocean pH or CO2 values. However, species living within dynamic coastal environments can naturally experience wide fluctuations in abiotic factors, suggesting their responses to stable pH conditions may not be reflective of either present or near-future conditions. Here we investigate the physiological responses of the mussel Mytilus edulis to variable seawater pH conditions over short- (6 h) and medium-term (2 weeks) exposures under both current and near-future OA scenarios. Mussel haemolymph pH closely mirrored that of seawater pH over short-term changes of 1 pH unit with acidosis or recovery accordingly, highlighting a limited capacity for acid–base regulation. After 2 weeks, mussels under variable pH conditions had significantly higher metabolic rates, antioxidant enzyme activities and lipid peroxidation than those exposed to static pH under both current and near-future OA scenarios. Static near-future pH conditions induced significant acid–base disturbances and lipid peroxidation compared with the static present-day conditions but did not affect the metabolic rate. These results clearly demonstrate that living in naturally variable environments is energetically more expensive than living in static seawater conditions, which has consequences for how we extrapolate future OA responses in coastal species.